Aproximacion a una estrategia general de evaluacion de la vivienda en comunidades marginales de las metropolis de paises en vias de desarrollo - Abaleron, C. A. (My University, 1988)
Evaluation is regarded as a highly complex, continuous process intended to improve the object-subject involved. In the case of marginal metropolitan neighborhoods, whose inhabitants live in conditions unfit for human beings, we must remember that the specific actors in the drama - the users of the area of operation - should be the main creators of their own individual and community development through the evaluation-improvement process. This paper provides a basis for discussing such an approach. -from English summary
Towards a general strategy for the evaluation of housing in marginal communities of metropolitan cities in developing countries
Keywords: evaluation; housing; marginal community; participation